Essays on Corporate Environmental Performance and Reporting - Dutta, Probal (Vaasan yliopisto, 2024)
This doctoral dissertation consists of three essays that examine different aspects of corporate environmental performance and corporate environmental reporting. The first essay investigates the association between corporate environmental performance and the adoption of voluntary sustainability assurance. The results reveal that companies, which are relatively better environmental performers in terms of water consumption and greenhouse gas (GHG) emissions, tend to purchase external sustainability assurance. The second essay explores the existence of any linkage between external assurance and the level of corporate climate change disclosures, a subset of corporate environmental reporting. The results indicate that external assurance is significantly and positively associated with the level of corporate climate change disclosures. The results demonstrate further that the level of corporate climate change disclosures is affected neither by the type of assurance providers (accounting firms vs non-accounting firms) nor by the type of financial auditors (Big4 financial auditors vs non-Big4 financial auditors). The third and final essay examines whether corporate environmental performance is associated with the corporate biodiversity reporting decision. Corporate biodiversity reporting is another subset of corporate environmental reporting. The findings confirm that companies with higher propensity to consume water and generate waste (two proxies for measuring corporate environmental performance) tend to report biodiversity-related information. The findings show further that propensity to emit GHGs (the third proxy for measuring corporate environmental performance) does not affect the decision to report biodiversity-related information as it possibly affects the disclosure of more relevant information such as corporate climate change-related information.

Tämä väitöskirja koostuu kolmesta esseestä, joissa tarkastellaan ympäristösuorituskyvyn ja ympäristöraportoinnin eri näkökulmia. Ensimmäisessä esseessä tutkitaan yritysten ympäristösuorituskyvyn ja vapaaehtoisen kestävän kehityksen varmennuksen välistä yhteyttä. Tulokset osoittavat, että yritykset, jotka ovat suhteellisesti ympäristöystävällisempiä veden kulutuksen ja kasvihuonekaasupäästöjen suhteen, hankkivat useammin ulkoisen kestävyysvarmennuksen. Toisessa esseessä tarkastellaan mahdollisia yhteyksiä ulkoisen varmennuksen ja yritysten ilmastonmuutosta koskevien tietojen julkistamisen tason välillä, joka on osa yritysten ympäristöraportointia. Tulokset osoittavat, että ulkoinen varmennus liittyy merkittävästi ja positiivisesti yritysten ilmastonmuutosta koskevien tietojen julkistamisen tasoon. Tulokset osoittavat lisäksi, että yritysten ilmastonmuutosta koskevien tietojen tasoon ei vaikuta varmennusten tarjoajien tyyppi (tilintarkastusyhteisöt vs. ei-tilintarkastusyhteisöt) eikä tilintarkastajien tyyppi (Big4-tilintarkastajat vs. ei-Big4-tilintarkastajat). Kolmannessa ja viimeisessä esseessä tarkastellaan, liittyykö yritysten ympäristösuorituskyvyn taso niiden biodiversiteettiraportointipäätöksiin. Yritysten biodiversiteettiraportointi on eräs yritysten ympäristöraportoinnin alaryhmä. Tulokset vahvistavat, että yritykset, joilla on suurempi taipumus kuluttaa vettä ja tuottaa jätettä (kaksi korvikemuuttujaa yritysten ympäristösuorituskyvyn tasolle), raportoivat useammin biodiversiteettiin liittyviä tietoja. Tulokset osoittavat lisäksi, että taipumus päästää kasvihuonekaasuja (kolmas korvikemuuttuja yritysten ympäristösuorituskyvyn tasolle) ei vaikuta päätökseen raportoida biodiversiteettiin liittyviä tietoja, koska se mahdollisesti vaikuttaa merkityksellisempien tietojen, kuten yritysten ilmastonmuutokseen liittyvien tietojen julkistamiseen.
Keywords: yritykset; ympäristönsuojelu; kestävä kehitys; ympäristö; ilmastonmuutokset; ympäristövaikutukset; raportointi; rahoitus; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|